Harmonizing Cultural Relativism with Universal Human Rights: Perspectives from Indonesia and the publication of Law No. 39 of 1999 concerning Human Rights, as part of the implementation of human rights in Indonesia - Russeng, A. (P3M Stia Al Gazali Barru and Meraja media, 2024)
[Full Paper] to pdf Copyright (c) 2024 Meraja journal